Analisis Pemikiran Syeikh Ahmad Sahibulwafa Tajul Arifin Yang Mendasari Metode Pemulihan Inabah [Analysis of Syeikh Ahmad Sahibulwafa Tajul Arifin’s Thinking Based On Inabah Recovery Method] - Abdul Manam, Mohamad; Julaily Aida, Jusoh; Lin, L.P (2020)
Inabah, founded by Syeikh Ahmad Sahibul Wafa Tajul Ariffin, the head of the boarding school of Suryalaya, East Coast, West Java, Indonesia, is an alternative method for recovering those involved in drug abuse and moral damages. This method has been recognized in several countries in the region and has gained national and international recognition. This method is based on the spiritual practice of Islam and is based on the thought of its founder as a religious leader. His thoughts have been scattered throughout some of his and his students' works, but this aspect has not been studied in detail by researchers. Therefore, this study was conducted to better understand the thinking of the founding figures underlying the formulation of the method. This study is a descriptive qualitative study and uses documentation method as data collection method. For this reason, the works produced by Syeikh Ahmad and his students' works which included his teachings on the subject, were studied and analysed using document analysis methods. The practices devised and formulated into this method of recovery, in addition to basic religious practices, have spiritual values that contribute to the purification of the soul, which is the basic philosophy of healing through the method of death, as explained by its founder. Research has found that Syeikh Ahmad based the method on the principle of "returning to God", through the method of purification of the soul (tazkiyat al-nafs), which is based on three main practices, such as bathing, prayer and remembrance, and is enshrined in qiyam al-layl, fasting, prayer and manners.